2014
DOI: 10.1074/jbc.m114.575340
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Heterogeneity in Site Recognition by the Structurally Homologous DNA-binding Domains of the ETS Family Transcription Factors Ets-1 and PU.1

Abstract: Background: ETS family transcription factors recognize DNA via structurally conserved DNA-binding domains that share limited amino acid homology. Results: DNA recognition by the ETS domains of Ets-1 and PU.1, two extreme sequence-divergent paralogs, was compared. Conclusion: Preferential hydration differentiates DNA recognition by Ets-1 and PU.1. Significance: Preferential hydration represents a potential mechanism for PU.1 regulation and its activity as a pioneer transcription factor in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 69 publications
(92 reference statements)
10
44
0
Order By: Relevance
“…Exogenous PU.1 expression in fibroblasts also induces accessible chromatin at de novo PU.1-binding sites in the inducible enhancers. PU.1 uses hydration to recognize target DNA and forms a long-lived complex relative to the other Ets factors, which use electrostatic interactions (Wang et al 2014). We speculate that the hydration-based recognition imparts the necessary adaptability for PU.1 to bind nucleosomal DNA.…”
Section: Pioneer Factors In Cell Programming During Developmentmentioning
confidence: 99%
“…Exogenous PU.1 expression in fibroblasts also induces accessible chromatin at de novo PU.1-binding sites in the inducible enhancers. PU.1 uses hydration to recognize target DNA and forms a long-lived complex relative to the other Ets factors, which use electrostatic interactions (Wang et al 2014). We speculate that the hydration-based recognition imparts the necessary adaptability for PU.1 to bind nucleosomal DNA.…”
Section: Pioneer Factors In Cell Programming During Developmentmentioning
confidence: 99%
“…56 Using physiologically compatible osmolytes to modulate the osmotic environment (water activity), the data indeed showed that high-affinity DNA binding by PU.1 was osmotic sensitive while binding by Ets-1 was not (Table 1). Moreover, the osmotic sensitivity of PU.1, wherein affinity was reduced by osmotic pressure, was dependent on the DNA sequence context, inferring a direct role of hydration in the specificity mechanism of PU.1.…”
Section: Role Of Molecular Hydration In Dna Recognition By Ets Proteinsmentioning
confidence: 93%
“…ETS paralogs are formally categorized into classes I-IV 27 by color in order from black, blue, orange, to yellow. (C) Differential sensitivity to osmotic pressure in site-specific binding by the ETS domains of PU.1 and Ets-1 as reported by Wang et al 56 The measured in vitro affinity is expressed as the logarithm of the dissociation constant (K D ). High-(solid symbols) and low-affinity DNA (open) refer to defined cognate (not nonspecific) sequences harboring the 5 0 -GGAA-3 0 consensus.…”
Section: Differential Tolerance To Cpg Methylationmentioning
confidence: 99%
See 2 more Smart Citations